Mixed mode fracture characterization of GFRP-concrete bonded interface using four-point single leg bending test. (15th September 2018) - Liu, Qinghui; Qiao, Pizhong; Lu, Linjun
Highlights: A 4-SLB specimen for mixed mode fracture of GFRP-concrete interface is proposed. Both the rigid and flexible joint models are used to calculate the compliance and ERR. The mixed mode fracture toughness of GFRP-concrete interface is experimentally obtained. The 4-SLB specimen design and data reduction procedures can be used to characterize hybrid material interface fracture. Abstract: A combined analytical and experimental study using a single leg bending specimen under four-point bend loading is conducted to characterize mixed mode fracture of glass fiber reinforced polymer (GFRP)-concrete bonded interface. Both the conventional composite (rigid joint) and interface deformable (flexible joint) bi-layer beam theories are used to calculate the compliance and energy release rate (ERR) of the proposed four-point single leg bending (4-SLB) specimens which are compared with and verified by the numerical finite element results. The results show that the flexible joint model results in more accurate compliance and ERR compared with the conventional composite bi-layer beam theory for the 4-SLB specimen due to the attribute of crack tip deformation. The calculated ERR by the flexible joint model can be reduced to that of the rigid joint one when the specimen is properly sized. Then, the designed 4-SLB specimens are utilized to measure the fracture toughness of GFRP-concrete bonded interface. To overcome the obstacle of low tensile strength of concrete and prevent the concrete substrate from premature fracture before the crack propagation of GFRP-concrete bonded interface takes place, the steel bars are used to reinforce the concrete substrate beams and a reduced section scheme at the interface is adopted. An aluminum beam is bonded to the thin GFRP plate so as to obtain different fracture mode ratios. The fracture toughness values of GFRP-concrete bonded interface under two different fracture mode ratios are obtained. The proposed 4-SLB specimen and data reduction procedures for the interface fracture toughness evaluation can be used to effectively characterize mixed mode fracture of hybrid material bonded interfaces.